Activation of Corticothalamic Layer 6 Cells Decreases Angular Tuning in Mouse Barrel Cortex - Pauzin, François Philippe; Schwarz, Nadja; Krieger, Patrik (Frontiers in Neural Circuits, 2019)
In the mouse whisker system, the contribution of L6 corticothalamic cells (L6 CT) to cortical and thalamic processing of the whisker deflection direction was investigated. A genetically defined population of L6 CT cells project to infragranular GABAergic interneurons that hyperpolarize neurons in somatosensory barrel cortex (BC). Optogenetic activation of these neurons switched BC to an adapted mode in which excitatory cells lost their angular tuning. In contrast, however, this was not the case with a general activation of inhibitory interneurons via optogenetic activation of Gad2-expressing cells. The decrease in angular tuning, when L6 CT cells were activated, was due to changes in cortical inhibition, and not inherited from changes in the thalamic output. Furthermore, L6 CT driven cortical inhibition, but not the general activation of GABAergic interneurons, abolished adaptation to whisker responses. In the present study, evidence is presented that a subpopulation of L6 CT activates a specific circuit of GABAergic interneurons that will predispose neocortex towards processing of tactile information requiring multiple whisker touches, such as in a texture discrimination task.